2016
DOI: 10.1002/cncr.30415
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelium expression of vascular cell adhesion molecule‐1 (VCAM‐1) is associated with an unfavorable prognosis in epithelial ovarian cancer (EOC)

Abstract: Background Mesothelium VCAM-1 expression in the metastatic epithelial ovarian cancer (EOC) microenvironment is induced by tumor and mediates tumor cell invasion. VCAM-1 imaging suggests expression during treatment is an indicator of platinum resistance. Here, we assess the potential prognostic significance of mesothelium VCAM-1 expression and prospectively evaluate whether soluble VCAM-1 (sVCAM-1) is a surrogate for mesothelium expression. Methods A retrospective review of EOC patients was performed to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…3D ), it is important to note that because of the limited number of patients used in this study, we considered chemoresistance as a relapse within 2-years post-chemotherapy treatment. Chemoresistance is often characterized as a relapse during the 6 months following the last chemotherapy treatment 45 , although longer periods of time have also been associated with increased chemoresistance 46 , 47 . Future studies using larger cohorts of patients will be needed to correlate expression of galectin signatures with a specific treatment and ideally a single agent will thus be needed to confirm our results using other criteria of chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…3D ), it is important to note that because of the limited number of patients used in this study, we considered chemoresistance as a relapse within 2-years post-chemotherapy treatment. Chemoresistance is often characterized as a relapse during the 6 months following the last chemotherapy treatment 45 , although longer periods of time have also been associated with increased chemoresistance 46 , 47 . Future studies using larger cohorts of patients will be needed to correlate expression of galectin signatures with a specific treatment and ideally a single agent will thus be needed to confirm our results using other criteria of chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ovarian cancers primarily metastasize through peritoneal dissemination from the primary tumor site to other distant organs including the omentum, colon, and liver. This metastatic process is often accompanied by ascitic fluid accumulation, which is associated with tumor metastasis and chemoresistance, further contributing to a poor survival rate in patients [ 2 , 3 ]. The current clinical therapy is to perform debulking surgery followed by chemotherapy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…suggested VCAM-1 as indicator for ovarian cancer response to platinum based chemotherapy, 11 and in a recent study, correlated serum sVCAM-1 with mesothelial VCAM-1 expression in 18 patients with ovarian cancer and were unable to identify serum sVCAM-1 as a surrogate for mesothelium expression. 12 To the best of our knowledge we didn't find any studies concerning sVCAM-1 and ovarian cancer recurrence. The role VCAM-1 in ovarian cancer is largely unclear, but it has been shown that mesothelial expression mediates tumor cell invasion.…”
Section: Discussionmentioning
confidence: 95%